PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA - RUDI HARTONO; EKO JUNI WAHYUDI (Jurnal Akademika, 2022)
The purpose of this research is to find out and analyze; a) the partial influence of leadership style and job satisfaction on employee work productivity, b) the simultaneous influence of leadership style and job satisfaction on employee work productivity, and c) dominant influencing factors on work productivity. The population in this study were all employees of the State Junior High School 1 Pakis Malang Regency a total of 75 people. in this study the researchers made the entire population (75 employees) as a sample. So the number of samples in this study was 75 people. The data analysis method used in this research is multiple linear regression analysis. research results show; a) leadership style variables and job satisfaction partially affect work productivity, b) leadership style variables and job satisfaction simultaneously affect work productivity, and c) job satisfaction variables are the most dominant variables affecting employee work productivity.Keywords: leadership style, job satisfaction, work productivity